2022
DOI: 10.1109/access.2022.3224047
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive-Based Gait Monitoring Technique for the Recognition of Knee Osteoarthritis Patients

Abstract: Knee osteoarthritis (Knee OA) is a degenerative disease that often perplexes the elderly and the whole society, and its timely recognition receives interest worldwide. However, traditional imaging examinations cannot reflect dynamic function nor implement long-term monitoring. To address this issue, this article suggests a piezoresistive-based gait monitoring method to recognize patients with Knee OA by assessing the plantar pressure signals during the subjects' walking, which is mobile, wearable, low-cost, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“… 70 , 73 , 74 , 76 , 77 , 80 , 81 However, it is worth noting that there is still a noticeable lack of work in the area of exercise assessment modules using this technology, as only one study was identified and categorized within this domain. 72 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 70 , 73 , 74 , 76 , 77 , 80 , 81 However, it is worth noting that there is still a noticeable lack of work in the area of exercise assessment modules using this technology, as only one study was identified and categorized within this domain. 72 …”
Section: Resultsmentioning
confidence: 99%
“…Wang et al presented a gait monitoring method to recognize patients with Knee Osteoarthritis (OA) by assessing the plantar pressure signals during walking. 72 Pressure signals were collected by a smart insole embedded with a flexible piezoresistive array (4 × 12 matrix). Their experiment involved 18 participants diagnosed with Knee OA and 22 control participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insole systems can estimate the distribution of the plantar pressure within a shoe [86] and also possess the capability of rendering a high number of recorded steps, thereby ensuring a long-term recording of gait, both indoors and outdoors [13]. Insole gait measurement systems are available in wide variants based on optoelectronic sensors, accelerometry and gyroscopes force-sensing resistors (FSRs), capacitive sensors, and piezoelectric sensors [87].…”
Section: Smart Insoles / Smart Shoesmentioning
confidence: 99%
“…Implementing machine learning in wearable devices will allow long-term and dynamic monitoring, which has already been used to detect plantar fasciitis [ 23 ], assess fall risk [ 24 , 25 ] and stroke rehabilitation [ 26 ], and monitor freezing of gait in patients with Parkinson’s disease [ 27 ]. Although Wang et al [ 28 ] used wearable insoles and machine learning to detect KOA, the progression of KOA could not be characterized in the study population, which included patients scheduled for surgery due to ineffectively conservative treatment as well as healthy subjects without symptoms of KOA. Other studies developed machine learning models to classify patients based on K-L grades [ 29 ] and WOMAC scores [ 30 ] using other gait parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%